Effect of Re-acidification on Buffalo Grass Rhizosphere and Bulk Microbial Communities During Phytostabilization of Metalliferous Mine Tailings - Honeker, Linnea K.; Gullo, Catherine F.; Neilson, Julia W.; Chorover, Jon; Maier, Raina M. (Frontiers in Microbiology, 2019)
Phytostabilized highly acidic, pyritic mine tailings are susceptible to re-acidification over time despite initial addition of neutralizing amendments. Studies examining plant-associated microbial dynamics during re-acidification of phytostabilized regions are sparse. To address this, we characterized the rhizosphere and bulk bacterial communities of buffalo grass used in the phytostabilization of metalliferous, pyritic mine tailings undergoing re-acidification at the Iron King Mine and Humboldt Smelter Superfund Site in Dewey-Humboldt, AZ. Plant-associated substrates representing a broad pH range (2.35 - 7.76) were sampled to 1) compare the microbial diversity and community composition of rhizosphere and bulk compartments across a pH gradient, and 2) characterize how re-acidification affects the abundance and activity of the most abundant plant growth promoting bacteria (PGPB; including N2-fixing) versus acid-generating bacteria (AGB; including Fe-cycling/S-oxidizing). Results indicated that a shift in microbial diversity and community composition occurred at around pH 4. At higher pH (>4) the species richness and community composition of the rhizosphere and bulk compartments were similar, and PGPB, such as Pseudomonas, Arthrobacter, Devosia, Pyllobacterium, Sinorhizobium, and Hyphomicrobium, were present and active in both compartments with minimal presence of AGB. In comparison, at lower pH (<4) the rhizosphere had a significantly higher number of species than the bulk (p <0.05) and the compartments had significantly different community composition (unweighted UniFrac; PERMANOVA p <0.05). Whereas some PGPB persisted in the rhizosphere at lower pH, including Arthrobacter and Devosia, they were absent from the bulk. Meanwhile, AGB dominated in both compartments; the most abundant were the Fe-oxidizer Leptospirillum and Fe-reducers Acidobacter and Acidiphilium, and the most active was the Fe-reducer Aciditerrimonas. This predominance of AGB at lower pH, and even their minimal presence at higher pH, contributes to acidifying conditions and poses a significant threat to sustainable plant establishment. These findings have implications for phytostabilization field site management and suggest re-application of compost or an alternate buffering material may be required in regions susceptible to re-acidification to maintain a beneficial bacterial community conducive to long-term plant establishment.